Lingual thyroid. A propos of a case - Yangali, Rubén (2003)
Lingual thyroid is an usual disease due to abnormal descent of the thyroid gland from the base of the tongue to its natural location during the embryonic stage. Diagnosis is mainly clinical complemented by image studies. This paper presents a case of lingual thyroid and literature review.